Social skills headteachers of schools centers. (European Journal of Education and Psychology, 2009)
This study aims to discover the extent of public school directors have developed and practiced their social skills, in performing his managerial functions, to plan and propose, based on the results, the training necessary additions to the exercise such leadership reach higher levels of efficiency. The sample was composed of 99 directors of schools of Public Elementary and Secondary Education, in the provinces of Granada and Almeria. The results obtained in this research provide us with reliable knowledge, hitherto non-existent, the profiles that characterize the current directors of schools, in their social and interpersonal skills. A summary of results is as follows: a) half of the principals (49%) obtained scores that are above the 75 centile, in behavior and social skills assertion b) nearly half of the directors in our sample are characterized by implementing social skills, through behavior, where the "self-expression", "say no", "initiate interactions” and “express their anger", are the most relevant components and c) the level of the center, the number of students at the school and the old director has made some significant differences.Key words: Social skills, school directors, managerial function, leadership.